Peningkatan Aktivitas Belajar IPS Siswa Melalui Model Pembelajaran Kooperatif Tipe Number Heads Together (NHT) di Kelas VII.4 SMP Negeri 5 Pariaman - Beatres, Irvan (Jurnal Pendidikan Nasional, 2021)
The problem in this study is the low learning activity of students in social studies subjects obtained by class VII.4 SMP Negeri 5 Pariaman City, this is due to the learning methods and student learning methods that are not appropriate. The purpose of this study was to obtain information about improving students' social studies learning activities through the Numbered Heads Together (NHT) cooperative learning model in Class VII.4 SMP Negeri 5 Kota Pariaman. The research was conducted in Class VII.4 SMP Negeri 5 Kota Pariaman. Types of classroom action research (CAR). The research subjects were class VII.4 SMP Negeri 5 Kota Pariaman with 31 students consisting of 13 female students and 18 male students. The research procedure for each cycle is planning, implementation, observation and reflection. The research instruments were observation, questionnaire, pretest, posttest, and daily notes. Data analysis technique is descriptive analysis. The results showed that the activity of asking questions in the first cycle was 67.7%, and in the second cycle it was 81.7%, which means an increase of 14.0%. The activity of answering in the first cycle is 61.1%, and in the second cycle it is 77.4% which means an increase of 16.1%. The response activity in the first cycle is 46.3%, and in the second cycle it is 64 .5% which means an increase of 18.2%. The activity of giving advice in the first cycle is 37.7%, and in the second cycle it is 59.1%, which means there is an increase of 21.4%. So the study concluded that the learning process using the Numbered Heads Together (NHT) cooperative learning model can improve the social studies learning activities of class VII.4 students of SMP Negeri 5 Pariaman City.